Pengaruh Penggunaan Terapi Antosianin terhadap Penyakit Alzheimer : Literature Review - Chintya Dorinda Chandany (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Alzheimer’s disease is the most common form of neurodegenerative disorder, characterized by cognitive decline, β-amyloid plaque accumulation, and oxidative stress in brain tissue. One promising alternative therapy is the use of anthocyanins, flavonoid compounds found in various red, purple, and blue-colored plants. This study aims to review the effectiveness of anthocyanins in preventing and slowing the progression of Alzheimer’s disease through a literature review. Articles published between 2014 and 2024 were selected from PubMed, Scopus, and Google Scholar databases, with inclusion criteria focusing on preclinical animal studies evaluating the effects of anthocyanins on neurodegenerative markers. The results show that anthocyanins, particularly pelargonidin and delphinidin, play a role in improving memory, reducing oxidative stress, and inhibiting β-amyloid plaque formation in animal models. Anthocyanins also enhance antioxidant enzyme activity and reduce neuronal apoptosis. These findings support the potential of anthocyanins as neuroprotective agents in Alzheimer’s therapy, although further clinical research is required to validate their efficacy in humans.